The study of bacterial contamination of drinking water sources: A case study of Mpraeso, Ghana - Omari, S.; Yeboah-Manu, D. (Internet Journal of Microbiology, 2012)
The study aimed at determining the presence, type, count and causes of bacterial contamination of water used for drinking and other domestic purposes in Mpraeso. Fifty-four (54) water samples (48 from 8 groundwater wells and 6 from a stream) were collected and analyzed for six months (both during the dry and raining seasons). The results showed that groundwater sources were as polluted as surface water. The detection of bacterial cells in the water sources means that some forms of treatment needed to be done before consumption. The mean count of total coliform and faecal coliform ranged from 299 - 2267 MPN colonies/100 ml water sample and 111 - 1235 MPN colonies/100 ml water sample, respectively. For the groundwater sources, the enterobacteriaceae species detected were Escherichia coli (8 wells), Enterococcus faecalis (8 wells), Klebsiella pneumoniae (6 wells), Enterobacter cloacae (5), Pseudomonas aeruginosa (3), and Proteus mirabilis (3). All these bacterial species were detected in the surface water samples. © Internet Scientific Publications, LLC., 1996 - 2013.
Keywords: Contamination; Enterobacteriaceae; Faecal coliform; Total coliform